E-Government and Digital Democracy a step towards a better Quality of Life in Algeria - Brahim Zirari; Youcef Souar (university Of Eloued جامعة الوادي, 2020)
Democracy and Governance have been seen as a process that protects human rights, ensure liberties and lead to economic development, hence, better quality of life. However, citizens in developing countries could not encounter the real democracy and good management, which led them to search for such freedom. In this context, Internet and Technology is playing a major role in countries development. Digital democracy and E Government are new concepts which mean that citizens can freely interact with various government departments at anytime and anywhere rapidly and with minimal efforts. Therefore, this study aims to analyse theatrically and statistically the nexus E Government, Digital Democracy and Quality of life in Algeria
Intervention
Keywords: Digital Economy; E-Government; Digital Democracy; Quality of Life; Algeria